1992
DOI: 10.1007/bf02636055
|View full text |Cite
|
Sign up to set email alerts
|

Partition coefficients for fatty acid esters in supercritical fluid CO2 with and without ethanol

Abstract: The complex nature of fish oils was exploited to study the dependence of structural factors upon fatty acid ester solubility in supercritical fluid carbon dioxide (SCF-CO2). Partition coefficients were determined for a number of components present in two mixtures of fatty acid ethyl esters derived from menhaden oil in SCF-CO2 at 60°C and 125 bar. Analogous data also were obtained for SCF-CO2 with 5% (why) ethanol added. The addition of ethanol was found to increase partition coefficients for all species, but r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 18 publications
2
10
0
3
Order By: Relevance
“…Probably, the EtOH dissolved in the SC-CO 2 results in the higher solubility of EE in the extraction medium. This supposition accords with the results presented by Nilsson and coworkers (16). They investigated partition coefficients (concentration of component i in the CO 2 phase/concentration of component i in the liquid phase) for fatty acid EE in SC-CO 2 with and without EtOH and found that the addition of EtOH increased the partition coefficients for all fatty acid EE studied.…”
Section: Resultssupporting
confidence: 82%
“…Probably, the EtOH dissolved in the SC-CO 2 results in the higher solubility of EE in the extraction medium. This supposition accords with the results presented by Nilsson and coworkers (16). They investigated partition coefficients (concentration of component i in the CO 2 phase/concentration of component i in the liquid phase) for fatty acid EE in SC-CO 2 with and without EtOH and found that the addition of EtOH increased the partition coefficients for all fatty acid EE studied.…”
Section: Resultssupporting
confidence: 82%
“…Liang and Yeh [5] determined the solubility of a modelled fish-like mixture of FAEEs, which varied from 1.7 to 121 mg/g CO 2 , for solvent densities of 342 and 723 kg/m 3 , respectively. Although some general similarities can be found among results reported in the literature, data concerning individual solubility and solvent selectivity differ for each fatty acid ethyl ester when comparing results obtained for oils from different sources [6], accordingly the behaviour of individual components has been suggested to depend on the overall mixture composition [3]. Since oil composition affects these parameters, new solubility and selectivity data must be obtained when a new raw material is studied, in order to ensure the proper design of a supercritical fractionation method.…”
Section: Introductionmentioning
confidence: 62%
“…El objetivo fue obtener ácidos grasos poliinsaturados, omega-3, a los cuales se les atribuye importantes beneficios para la salud. La destilación a vacío utilizada normalmente en procesos de concentración y separación requiere altas temperaturas que conllevan a alteraciones o descomposiciones de los áci-dos grasos (Nilsson et al, 1992).…”
Section: Extracción Y Fraccionamiento De Lípidosunclassified
“…Otros estudios se han centrado en determinar la solubilidad de ácidos grasos y triglicéridos en dióxido de carbono (Bamberger et al, 1988;Nilsson et al, 1992). También fue estudiada la solubilidad de diferentes ácidos: esteárico y oleico y triglicéridos como tributirina, tripalmitina, triestearina, trioleína y trilinoleína en un intervalo de temperaturas de 40 o C -80ºC y presiones de 80 a 250 bar (Chrastil, 1982).…”
Section: Extracción Y Fraccionamiento De Lípidosunclassified